Synthesis of large (2+3) salicylimine cages with embedded metal-salphen units [data] - Uhrmacher, Fabian; Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
Shape-persistent trinuclear Ni(II)- and Pt(II)-cage compounds with large cavities have been synthesized by using bissalicylaldehyde struts that con...
Im Titel steht der Ausdruck "2+3" in eckiger Klammer
Gesehen am 09.02.2022
Keywords: Forschungsdaten; Datenbank